Plantar pressure distribution analysis of alpine and boardercross snowboarders's carving turns - Lee, C. H.; Back, J.; Lee, J.; Panday, S. B.; Lim, Y.-T. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Plantar pressure distribution analysis of alpine and boarder-cross snowboarder's carving turn was performed to provide instructors and snowboarders with scientific and quantitative data for evaluation of the turn. Snowboarders from Korean National Team for 2018 Pyeongchang Winter Olympics were chosen as subjects. To allow on-snow measurements of plantar pressure distribution, the boots were outfitted with pressure sensitive insoles. The carving turn section was divided into 5 events and 4 phases of which force, maximum pressure, and plantar contact area were analyzed. Comprehensive kinematical analysis was conducted which indicated the major features of pressure distribution in two different sporting events. The proposed results can be used as a reference for improvement of the training method in snowboarding.